X-linked histone demethylase kdm6a as a candidate to mediate sex chromosome effects on Ngn3 dimorphic expression in the developing brain - Cabrera Zapata, L. E. (2019)
Fil: Cabrera Zapata, Lucas Ezequiel. Consejo Nacional de Investigaciones Científicas y Técnicas. Instituto de Investigación Médica Mercedes y Martín Ferreyra; Argentina.